2020
DOI: 10.1177/2150132719901209
|View full text |Cite
|
Sign up to set email alerts
|

Can Flu-Like Absenteeism in Kindergartens Be Reduced Through Hand Hygiene Training for Both Parents and Their Kindergarteners?

Abstract: Background: Hand hygiene has been found as an effective method to prevent the spread of infectious diseases. Parents, however, were found to have inadequate knowledge, reporting skills, and parenting practices related to seasonal influenza. The aim of our study was to investigate if there was any correlation between the flu infection among parents and their kindergarteners and ascertain the effectiveness of using hand hygiene interventions in kindergartens to lower kindergarteners’ absenteeism attributable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The major aim of health education for children should be to help them to make the right choices or decisions related to their health behavior. A quasi-experimental study conducted in Hong Kong found that kindergarten students with strong parenting and proper HH compliance can help to reduce flu-like absenteeism among students [ 17 ]. Another observational study assessed the changes in knowledge and handwashing practices after providing a thematic lecture on hygiene for kindergarten children and reported that the proportion of participants capable to complete handwashing procedures is low [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The major aim of health education for children should be to help them to make the right choices or decisions related to their health behavior. A quasi-experimental study conducted in Hong Kong found that kindergarten students with strong parenting and proper HH compliance can help to reduce flu-like absenteeism among students [ 17 ]. Another observational study assessed the changes in knowledge and handwashing practices after providing a thematic lecture on hygiene for kindergarten children and reported that the proportion of participants capable to complete handwashing procedures is low [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The setting of these studies varied from the household setting ( n = 4) ( 14 , 16 , 23 , 27 ), over the hospital and healthcare facilities ( n = 7) ( 7 , 9 , 10 , 24 26 , 28 ), schools ( n = 6) ( 15 , 17 , 18 , 29 – 31 ), and University setting ( n = 2) ( 20 , 22 ), to the corporation worksites ( n = 2) ( 8 , 21 ) and one study was performed on Hajj pilgrims ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…All 21 studies implemented at least one intervention of a promotional program with educational sessions or informative content and reminders. The educational sessions were characterized by education of the target group through either verbally communicated hand and respiratory hygiene lessons (e.g., instructions by telephone, on the internet, or face-to-face), with training or instructions on how and how frequent to practice hand hygiene and to use face masks or in combination with written or visual media (e.g., information leaflets, posters, video/live demonstration) ( 7 , 9 , 15 , 17 20 , 31 ). In addition to that, some studies consisted of the provision of hand hygiene materials, either soap ( 14 , 19 ), alcohol-based hand sanitizers ( 14 , 15 , 18 20 , 31 ), face masks ( 14 , 19 , 20 ), provided by the researchers to every participating individual ( 14 , 19 , 20 ) or to be shared within their cluster or with others in case of provision at a common place (e.g., common courtyards or school toilets) ( 15 , 18 , 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Parents have a great influence over their children’s health promotion behaviours [ 37 , 38 ]. With growing evidence about the effect of combined interventions on preventing the spread of infectious diseases in general and intestinal helminths in particular [ 20 22 ], the parental engagement model tested in this study is a valuable addition to sanitation and handwashing interventions targeting school children.…”
Section: Discussionmentioning
confidence: 99%